REALISASI TEMPORALITAS, ASPEKTUALITAS, DAN MODALITAS DALAM BAHASA INGGRIS DAN BAHASA INDONESIA - Oktavianti, Ikmi Nur; Prayogi, Icuk (Adabiyyāt: Jurnal Bahasa dan Sastra, 2018)
In linguistic typology, the terms “tense”, “aspect”, “mood/modality” are commonly used and recognized as verb paradigms or verbal systems (morphosyntactically) as well as verb semantic aspects (semantically) in describing language characteristics. Those terminologies, however, are treated as equivalents, while theoretically they remain problematic. Tense and aspect belong to grammatical categories, while modality is a semantic notion. There is also another term ‘mood’ that is often misunderstood as the synonym of modality of which they are basically two distinct yet related concepts. This paper then aims at revisiting those terms above by using the terms “temporality’, “aspectuality, and “modality” and investigating the realizations of those notions in English and Indonesian in order to obtain comprehensive understanding. This study employed contrastive analysis to compare English and Indonesian. The data were collected from two synchronic corpora, Corpus of Contemporary American English (COCA) for English data and Wortschatz Leipzig Corpora Collection (WLCC) for Indonesian data. The results of the analysis show that English and Indonesia have distinct realizations of temporality, aspectuality, and modality of which English is more various in manifesting temporality, while Indonesian is more various in manifesting aspectuality. As for modality, English has more realizations, including core modals and quasi-modals. It can be concluded that basically English is morphosyntactically and syntactically richer than Indonesian, but Indonesian is morphologically richer than English.